Desarrollo de un proceso sistemático para la integración BIM en la planificación de los maestros de obras de Puerto Colombia Atlántico Colombia (2025)
Building Information Modeling (BIM) has transformed construction by integrating multidimensional information in a collaborative environment, improving project planning and management. However, its implementation in the Atlantic region, especially in Puerto Colombia, faces challenges related to training and adoption by construction foremen. Although BIM has gained global recognition, its application in the Colombian Caribbean remains limited by technological, economic, and cultural barriers. This research aims to develop a systematic process to facilitate the incorporation of BIM into the planning of construction foremen in Puerto Colombia. A mixed-methods, descriptive approach was employed, using surveys with open-ended and closed-ended questions to analyze both quantitative and qualitative data. The quantitative component assesses current planning methodologies and the level of knowledge about BIM, while the qualitative component explores perceptions, experiences, and cultural obstacles that influence its implementation. The survey was administered to a representative sample of construction foremen to design a procedure that allows them to record and update project progress in an organized manner compatible with BIM models. The aim is to reduce resistance to change, strengthen digital training, and foster collaboration among academic institutions, construction companies, and government entities. In this way, research can contribute to the modernization, efficiency, and competitiveness of the construction sector in Puerto Colombia.